Serelaxin Protects H9c2 Cardiac Myoblasts against Hypoxia and Reoxygenation-Induced Damage through Activation of AMP Kinase/Sirtuin1: Further Insight into the Molecular Mechanisms of the Cardioprotection of This Hormone - Virginia Zizi; Matteo Becatti; Daniele Bani; Silvia Nistri (MDPI AG, 2024)
Serelaxin (RLX), namely the human recombinant Relaxin-2 hormone, protects the heart from ischemia/reperfusion (I/R)-induced damage due to its anti-inflammatory, anti-apoptotic and antioxidant properties. RLX acts by binding to its specific RXFP1 receptor whereby it regulates multiple transduction pathways. In this in vitro study, we offer the first evidence for the involvement of the AMP kinase/Sirtuin1 (AMPK/SIRT1) pathway in the protection by RLX against hypoxia/reoxygenation (H/R)-induced damage in H9c2 cells. The treatment of the H/R-exposed cells with RLX (17 nmol L−1) enhanced SIRT1 expression and activity. The inhibition of SIRT1 signaling with EX527 (10 µmol L−1) reduced the beneficial effect of the hormone on mitochondrial efficiency and cell apoptosis. Moreover, RLX upregulated the AMPK pathway, as shown by the increase in the expression of phospho-AMPK-activated protein. Finally, AMPK pathway inhibition by Compound C (10 and 20 μmol L−1) abrogated the increase in SIRT1 expression induced by RLX, thus suggesting the involvement of the AMPK pathway in this effect of RLX. These results strengthen the concept that RLX exerts its cardioprotective effects against H/R-induced injury through multiple pathways which also include AMPK/SIRT1. These new findings support the use of RLX or RLX-derived molecules as a promising therapeutic for those diseases in which I/R and oxidative stress play a pathogenic role.